Fat and Cholesterol Content of Some Fish and Shellfish of Bay of Bengal - Uddin, Musleh; Jahan, Parveen; Uddin Ahmed, Moin (Asian Journal of Chemistry, 2010)
Twenty nine samples of fish and shellfishes from Bay of Bengal were analyzed to know their fat and cholesterol contents. Cholesterol and fat contents were significantly different among various families of fish and shellfish. Higher content of cholesterol was observed in shellfish than in fish. Moreover, fresh water fish contained lower amount of cholesterol than marine fish.